Transformative Experience, Awareness Growth, and the Limits of Rational Planning. Issue 5 (10th December 2022) - Steele, Katie; Stefánsson, H. Orri
Abstract: Laurie Paul argues that, when it comes to many of your most significant life-changing decisions, the principles of rational choice are silent. That is because, in these cases, you anticipate that one of your choice options would yield a transformative experience . We argue that such decisions are best seen as ones in which you anticipate awareness growth . You do not merely lack knowledge about which possible outcome will arise from a transformative option; you lack knowledge about what are the possible outcomes. We show how principles of rational choice can be extended to cases of anticipated awareness growth.